Cardio-respiratory values during recovery from exercise in soccer Spanish leagues. (12th October 2018) - Ramos-Álvarez, Juan José; Maffulli, Nicola; Bragazzi, Nicola Luigi; Ardigò, Luca Paolo; Jiménez-Herranz, Elena; Naranjo-Ortiz, Cristina; Padulo, Johnny; Calderón Montero, Francisco Javier
Abstract: Objective : In this cross-sectional study, we compared Spanish division one ( n   =  114) and division two ( n   =  80) soccer players in terms of their cardio-respiratory response during recovery following a maximum laboratory effort test. Approach : Following the maximum laboratory effort protocol, we measured oxygen consumption ( ), heart rate (HR), and ventilation ( ) during recovery. Main results : Over the first 60 s of recovery, no significant differences were seen in either (28.7 versus 28.3 ml/kg/m, in division one and two players, respectively), HR, or ( p   >  0.05). After 90 s, however, significant differences appeared between the players of the two divisions ( p   <  0.01), although not among playing positions. Significant differences in (21.1 versus 26.0 ml/kg/m, in division one and two players, respectively) and HR were still apparent at 180 s into the recovery period. The change in professional soccer players' cardio-respiratory values over the recovery period following maximum effort are independent of the position played, but are associated with the division in which a player competes. Second division players show significantly higher and HR values than first division players at 180 s into the recovery period. Significance : These differences might influence performance in soccer and in other athletes whose sports require intermittent bouts of maximum effort and consequently times to repeat high-intensity efforts as short as possible.